2004
DOI: 10.3949/ccjm.71.4.353
|View full text |Cite
|
Sign up to set email alerts
|

Head injury: which patients need imaging? Which test is best?

Abstract: Some patients with head injuries definitely need to undergo an imaging study-usually computed tomography (CT). Most, however, are in a category of "apparently mild" injury, and controversy continues about which of them need to undergo imaging studies to rule out intracranial injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
16
0
2
Order By: Relevance
“…Complications of mild head trauma are unusual, but in rare cases it can be life-threatening and require neurosurgical intervention (0.4%-1.0%). Cranial computed tomography (CCT) scan is the imaging study of choice, although some considerations about cost, medical staff, patient sedation and proper devices limit its routine use in children and adolescents [7][8][9][10][11] . There are some divergences regarding CCT scan and skull radiograph indications in pediatric population 4,6,7,10,11 .…”
mentioning
confidence: 99%
“…Complications of mild head trauma are unusual, but in rare cases it can be life-threatening and require neurosurgical intervention (0.4%-1.0%). Cranial computed tomography (CCT) scan is the imaging study of choice, although some considerations about cost, medical staff, patient sedation and proper devices limit its routine use in children and adolescents [7][8][9][10][11] . There are some divergences regarding CCT scan and skull radiograph indications in pediatric population 4,6,7,10,11 .…”
mentioning
confidence: 99%
“…In acute settings imaging helps in accurate localization of any cerebral damage. During first 24 hours of injury conventional CT scan is considered to be imaging modality of choice because of its availability, lesser imaging time, able to perform on disturbed patients and cost effective (2). CT scan is superior in detecting any bony damage and bleeding in brain parenchymal or meninges or spaces (3).…”
Section: Location Of Abnormal Ct Signsmentioning
confidence: 99%
“…CT characteristics not only widely accepted for descriptive purposes, but also increasingly being used as major predictor of outcome in TBI. Following TBI the pathological findings on CT scan that is represented by scoring system is oriented in predicting prognification of outcome (2,4,12,13). Various studies and the international guidelines on prognosis include the CT scoring system as a major outcome predictor13.…”
Section: Introductionmentioning
confidence: 99%
“…According to our findings, head injury was commonly associated to the use of CT and remained essentially stable during the study period. Cranial CT scanning is considered to be the imaging modality of choice for the rapid and reliable diagnosis of traumatic head injuries (9). Several retrospective studies conclude that CT is indicated in all patients with minor head injury (10)(11).…”
Section: Indicationmentioning
confidence: 99%